The Long Tradition of Mulud as a Media for Religious Character Education Based on Local Wisdom in Elementary School Extracurricular Activities in Serang City - Sujanah, Nanah; Maisaroh, Ima; Muhyidin, Asep; Jamaludin, Ujang (Future Science, 2025)
The Panjang Mulud tradition is a religious cultural heritage of the Banten community, celebrated in conjunction with the Prophet Muhammad's birthday. This research aims to examine the potential of the Panjang Mulud tradition as a medium for religious character education based on local wisdom, particularly in elementary school environments. Using a qualitative literature study approach, this article finds that the values of monotheism, worship, ethics, and Islamic brotherhood contained in the Panjang Mulud tradition are highly relevant for implementation in extracurricular activities. The results show that integrating these values strengthens students' Islamic identity and enriches character education methods. This article recommends cross-party collaboration for optimizing the role of local traditions in shaping students' character